Effect of temperature and lactic acid bacteria on the surface growth of Geotrichum candidum - Anna Hudecová; Ľubomír Valík; Denisa Liptáková; Jana Pelikánová; Michal Čižniar (Czech Journal of Food Sciences, 2011)
The surface growth of Geotrichum candidum isolated from ewes' lump cheese was studied on pure agar medium and that inoculated with Lactobacillus rhamnosus GG and L. paracasei subsp. paracasei CCM 1753. The colony growth rates of fungus calculated from the growth curves were modelled in relation to temperature by the cardinal temperature model with inflection (CTMI). The following cardinal values resulted from the secondary model: Tmin = -3°C, Topt = 27.6°C, and Tmax = 35.4°C and optimal colony growth rate µopt = 5.34 mm/day. A quantitative study also showed that the simultaneous growth of L. rhamnosus GG and L. paracasei subsp. paracasei CCM 1753 had either no or only a slight effect on the fungal growth rates, respectively. These results pointed out that other intrinsic or extrinsic factors should be applied for the protection of fresh cheeses against the undesirable growth of G. candidum.